Analisis Kemampuan Siswa dalam Pemahaman Membaca Fokus Berpikir Literal di Kelas III Sekolah Dasar - Muhammad Zikrisyah; Chandra Chandra; Salmaini Safitri Syam (Lembag, 2025)
This study aims to describe the ability to read literal thinking comprehension of grade III students of SDIT Ridhotullah through cognitive and psychomotor assessments. The method used is quantitative descriptive with five students as subjects. The instruments consist of cognitive tests (multiple choice, short answers, essays) and psychomotor assessments (reading aloud, arranging sequences of events). The results show that all students are in the very good category for the cognitive aspect, with scores of 88–96%. In the psychomotor aspect, four students are in the very good category and one student is in the good category. This finding emphasizes the importance of developing assessment instruments that are appropriate to the characteristics of student development to improve basic literacy.